Conceptualizing Chinese Collaborative Planning in the Digital Era: Institution Design, Power Relations, and Public Spheres - Lin, Yanliu (Taylor and Francis, 2026)
This chapter conceptualizes collaborative planning in China as a hybrid practice solution that combines authoritarian deliberation, multi-level institutional design, asymmetric power relations among diverse actors, and fragmented public spheres to address increasing complexities. Institutional innovations for collaborative planning are often developed to tackle specific governance problems. Institutional design, including formal and informal rules, addresses governance issues that cross horizontal, vertical, and territorial levels, with accountability emerging as a key challenge for effectiveness. Power dynamics are shaped by the diversity of actors, various power sources, the arenas in which power is exercised, and actors’ strategies and interests. While the digital public sphere is fragmented and creates new forms of power inequality, it also creates opportunities for marginalized voices through discourse and framing strategies to gain legitimacy. Rather than adopting a normative perspective, this chapter advances a context-sensitive conceptualization of collaborative planning, acknowledging its instrumental rationales, digital transformations, and complex negotiation of legitimacy in authoritarian contexts.
Keywords: General Environmental Science; General Social Sciences; General Engineering; General Arts and Humanities